Dan-Lou Prescription Inhibits Foam Cell Formation Induced by ox-LDL via the TLR4/NF-κB and PPARγ Signaling Pathways - Gao, Li-Na; Zhou, Xin; Lu, Yu-Ren; Li, Kefeng; Gao, Shan; Yu, Chun-Quan; Cui, Yuan-Lu (Frontiers in Physiology, 2018)
Atherosclerosis is the major worldwide cause of mortality for patients with coronary heart disease. Many traditional Chinese medicine compound prescriptions for atherosclerosis treatment have been tried in patients. Dan-Lou prescription, which is improved from Gualou-Xiebai-Banxia decoction, has been used to treat chest discomfort (coronary atherosclerosis) for approximately 2,000 years in China. Although the anti-inflammatory activities of Dan-Lou prescription have been proposed previously, the mechanism remains to be explored. Based on the interaction between inflammation and atherosclerosis, we further investigated the effect of Dan-Lou prescription on macrophage-derived foam cell formation and disclosed the underlying mechanisms. In the oxidative low-density lipoprotein (ox-LDL) induced foam cells model using murine macrophage RAW 264.7 cells, the ethanol extract from Dan-Lou prescription (EEDL) reduced ox-LDL uptake and lipid deposition by inhibiting the protein and mRNA expression of Toll-like receptor (TLR)4 and scavenger receptor (SR)B1. After stimulation with ox-LDL, the metabolic profile of macrophages was also changed, while the intervention of the EEDL mainly regulated the metabolism of isovalerylcarnitine, arachidonic acid, cholesterol, aspartic acid, arginine, lysine, L-glutamine and phosphatidylethanolamine (36:3), which participated in the regulation of the inflammatory response, lipid accumulation and cell apoptosis. In total, 27 inflammation-related gene targets were screened, and the biological mechanisms, pathways and biological functions of the EEDL on macrophage-derived foam cells were systemically analyzed by Ingenuity Pathway Analysis system (IPA). After verification, we found that EEDL alleviated ox-LDL induced macrophage foam cell formation by antagonizing the mRNA and protein over-expression of PPARγ, blocking the phosphorylation of IKKα/β, IκBα and NF-κB p65 and maintaining the expression balance between Bax and Bcl-2. In conclusion, we provided evidences that Dan-Lou prescription effectively attenuated macrophage foam cell formation via the TLR4/NF-κB and PPARγ signalling pathways.